The content validity of the ANMS GCSI-DD in patients with idiopathic or diabetic gastroparesis - Dennis A. Revicki; Sara Lavoie; Rebecca M. Speck; Jorge Puelles; Braden Kuo; Michael Camilleri; Cristina Almansa; Henry P. Parkman (SpringerOpen, 2018)
Abstract Background The American Neurogastroenterology and Motility Society Gastroparesis Cardinal Symptom Index-Daily Diary (ANMS GCSI-DD) was developed to meet Food and Drug Administration (FDA) recommendations for patient-reported outcome (PRO) endpoints in gastroparesis studies, including therapeutic trials. The current version of the ANMS GCSI-DD contains five items pertaining to nausea, early satiety, post-prandial fullness, upper abdominal pain, and vomiting. The specific aims of this study were to determine if the appropriate symptoms are included in the ANMS GCSI-DD and to assess the content validity in patients with idiopathic (IG) and diabetic gastroparesis (DG). Methods Patients diagnosed with IG or DG were recruited by five clinical sites in the United States for a cross-sectional, qualitative study involving one-on-one in-person concept elicitation and cognitive debriefing interviews. Concept elicitation included open-ended questions to elicit patients' symptoms and impacts of gastroparesis, while cognitive debriefing was designed to assess the comprehensiveness of the ANMS GCSI-DD and clarity of the instructions, items, and response scales. The interviews were audio-recorded and transcribed. Transcripts were analyzed using a content analysis approach with ATLAS.ti. Results Of 25 patients interviewed, 15 (60%) had IG and 10 (40%) DG. Mean age of the sample was 42.3 years (range: 20-70 years), and most patients were female (n = 19, 76%) and white (n = 19, 76%). During concept elicitation, patients endorsed the following signs and symptoms as relevant and important to their condition: early satiety (n = 25, 100%), post-prandial fullness (n = 25, 100%), nausea (n = 22, 88%), upper abdominal pain (n = 18, 72%), vomiting (n = 15, 60%), and bloating (n = 11, 44%). Many patients (n = 20, 80%) experienced day-to-day symptom change. During cognitive debriefing, patients confirmed the ANMS GCSI-DD content was comprehensive and reflective of their gastroparesis experience. Patients could easily select a response option and describe how they arrived at their answers. Overall, patients found the instrument's instructions, recall period, items, and response options clear and understandable. Conclusions The ANMS GCSI-DD was easily understood, found to contain the most important symptoms for patients with IG and DG, and no changes were recommended. Results support the content validity of the ANMS GCSI-DD for clinical trials and clinical care among IG or DG patients.